Assessing the growth and spatial-temporal evolution of China's digital economy - Lin Li; Le Xiaobing; Brahim Chekima (AESS Publications, 2025)
This research examines the assessing growth and spatial-temporal evolution of China’s digital economy. There exists a notable imbalance in the advancement of the digital economy across different districts in China. To gain a comprehensive understanding of China's digital economy’s development, this study establishes an evaluation system to assess the level of digital economic growth. By employing metrics such as the difference coefficient, Moran’s I, and Moran scatter plot, the research delves into the spatial distribution characteristics of China's regional digital economy using provincial panel data from 2013 to 2020. The findings reveal a consistent alignment between the distribution of the regional digital economy and the country's geographical layout, with the development level regularly decreasing from east to west. The decreasing overall difference coefficient indicates a gradual convergence in the development level of the regional digital economy. Moreover, substantial spatial autocorrelation is observed, suggesting the formation of a relatively stable spatial pattern in the development of the digital economy.